Intrinsic Value Evaluation of CNPC: A Comprehensive Analysis - Cao, Yiliang (International Journal of Global Economics and Management, 2024)
This paper aims to evaluate the intrinsic value of China National Petroleum Corporation (CNPC) through a specially designed valuation system tailored to the unique characteristics of the Chinese oil industry. Utilizing an entropy method to calculate the company’s valuation premium rate, referred to as the "China-Specific Valuation Premium Rate" (CSVPR), the analysis incorporates various valuation models, including the Free Cash Flow to Firm (FCFF) model, Dividend Discount Model (DDM), Economic Value Added (EVA) model, and Relative Valuation model.